Postharvest preservation of citrus fruits (Kinnow) by gamma irradiation and its impact on physicochemical characteristics - Abdullah, Roheena; Rashid, Saba; Naz, Shagufta; Iqtedar, Mehwish; Kaleem, Afshan (Progress in Nutrition, 2018)
Citrus fruit (Kinnow) has several beneficial health and nutritive properties. Several techniques have been used to preserve postharvest quality of citrus fruits. Exposing foods to gamma radiation delays spoilage and increases protection by eliminating or lowering pathogenic bacteria. In the present study Kinnow fruit were exposed to radiation dose of 0.0, 0.25, 0.50, 0.75, 1.0, 1.5 and 2.0 kGy. Physicochemical and microbial analysis was performed on control and irradiated samples stored at both ambient and refrigerated temperature on weekly intervals. No significant change was observed in physicochemical properties of Kinnow at optimum dose, epiphytic microbial flora reduced in irradiated samples than control samples. The radiation dose of 1.5 kGy along with refrigerated storage extended the shelf-life of Kinnow for 1week without affecting sensory and physicochemical properties.